APPLICATION OF NSSC PULPING TO SUGARCANE BAGASSE - Alireza Khakifirooz; Ahmad Samariha (BioResources, 2011)
The NSSC pulping process was investigated to produce pulp from bagasse for corrugating board manufacture. The chemical contents including cellulose, lignin, ash, and extractives soluble in alcohol-acetone measured 55.75, 20.5, 1.85, and 3.25, respectively. The average fiber length, fiber diameter, lumen width, and cell wall thickness of bagasse were 1.59 mm, 20.96, 9.72, and 5.64 μm, respectively. The optimum conditions, with a yield of 74.95%, were achieved using 20 percent chemicals on the basis of sodium oxide, cooking temperature of 170 °C, and cooking time of 30 minutes. Pulp was refined to freeness 345 and 433 mL CSF according to Canadian standards. 127 g m-2 handsheets from both pulps were made and strength properties measured. Statistical analysis of results indicated that paper derived from freeness 345 and 433 mL CSF had better strength properties in all indices in comparison with NSSC pulp from hardwoods produced at Mazandaran Pulp and Paper factory, Iran.